Development and initial validation of Sport Experiences Questionnaire (SEQ). (15th March 2019) - Luiggi, Maxime; Maïano, Christophe; Griffet, Jean
Abstract: To understand sport participation, multiple scales exist to examine why people participate. However, no questionnaires have been devised to assess what sport experiences people declare most pleasurable. This study aimed to develop and provide initial validation of a scale measuring adolescent athletes' retrospective reports of pleasure in three modern sports experiences: competition, progress, and risk taking. The first study examined the validity of a pool of 25 items. The second study examined the factor structure and reliability of a 14-item questionnaire among a sample of adolescent athletes, the measurement invariance across sexes and context of participation, and the differential item functioning and possible latent mean differences as a function of age. Results showed initial evidence regarding the reliability and validity of the scale. They showed invariance of the model across sexes and context of participation. This questionnaire could be used by sports federations and could help the development of sport promotion programs.